Cardiomyopathy in western Denmark. Issue 3 (September 1984) - Bagger, J P; Baandrup, U; Rasmussen, K; Møller, M; Vesterlund, T
Abstract : A retrospective study was carried out to assess the incidence of cardiomyopathy in western Denmark (Jutland and Funen) (population 2 798 000) during a two year period (1980-81). The WHO/ISCF classification was strictly followed, and rigid criteria for exclusion and inclusion of patients were adopted. Thus cases in which specific heart muscle disorders (myocarditis, alcoholic heart disease, hypertension etc) were merely suspected were excluded. Forty one patients had dilated cardiomyopathy (overall incidence 7.3/10(6) population/year) and 20 hypertrophic cardiomyopathy (overall incidence 3.6/10(6) population/year). In men aged 40-59 years the occurrence of dilated cardiomyopathy was 23.4/10(6) population/year. Only one case of Löffler's endomyocardial disease was diagnosed during the study period. Since the investigation was retrospective and was a study of diseased persons and not a population, and since a specific set of criteria for exclusion and inclusion was rigidly applied, the results represent the minimum frequency of these diseases.